2018
DOI: 10.1155/2018/7459141
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Three-Dimensional Hypersonic Inward-Turning Inlet with Tri-Ducts for Combined Cycle Engines

Abstract: The operation of a propulsion system in terms of horizontal takeoff/landing and full-speed range serves as one of the main difficulties for hypersonic travelling. In the present work, a three-dimensional inward-turning inlet with tri-ducts for combined cycle engines is designed for the operation of three different modes controlled by a single rotational flap on the compression side, which efficiently simplifies the inlet structure and the flap control mechanism. At high flight speed between Mach 4 and 6, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although the Mach numbers are different, the results may still be reliable enough, as done in Ref. [27]. Figure 8 shows the flow field of sample ID-001.…”
Section: š‘€š‘Ž Sin (Ī²mentioning
confidence: 85%
“…Although the Mach numbers are different, the results may still be reliable enough, as done in Ref. [27]. Figure 8 shows the flow field of sample ID-001.…”
Section: š‘€š‘Ž Sin (Ī²mentioning
confidence: 85%
“…Combined Inlet Model. The three-dimensional inwardturning multiducted combined inlet was proposed by Zhu et al [37,38]. Cai et al [39] confirmed that its geometric aerodynamic characteristics can meet the requirements of the propulsion system, which is capable of continuous oper-ation in a wide speed range.…”
Section: Inlet Model and Cfd Datasetmentioning
confidence: 99%
“…A three-dimensional inwardturning tetraduct inlet for turbine-based combined cycle engines has been designed in the present paper based on the methodology proposed in Ref. [12]. But different from the previous upper arrangement of a single duct for the turbine engine (referred to as T-duct hereafter) in Ref.…”
Section: Numerical and Experimental Setupsmentioning
confidence: 99%
“…But different from the previous upper arrangement of a single duct for the turbine engine (referred to as T-duct hereafter) in Ref. [12], two T-ducts are adopted in this work in order to meet the mass requirement of the combined cycle engine. The configuration of the tetraduct inlet is shown in Figure 1, where the two side ducts denoted by T are the flow paths for the turbine engine, the upper duct corresponds to the flow path for the ejector-ramjet engine (referred to as E-duct hereafter), and the lower duct is the flow path for the scramjet engine (referred to as S-duct hereafter).…”
Section: Numerical and Experimental Setupsmentioning
confidence: 99%